A CORRELATION BETWEEN LINGUISTIC COMPETENCE AND SPEAKING PERFORMANCE OF THE INTERMEDIATE STUDENTS’ - Idan Shalahuddin As (Universitas PGRI Palembang, 2023)
This study aims to determine the effect of linguistic competence on the speaking performance of secondary students in learning English. The research method used a qualitative descriptive. data collection techniques used Observation , Questionnaires, Interview based on the results of the analysis it can be said that students have problems in speaking analyzed there are 24 students who know or know about linguistic competence, 10 students didn't did not know about linguistic competence and 2 students did not fill out the questionnaire because they take the test.